The intercontextuality of self and nature in Ludwig Tieck's early works - Sullivan, Heather I. 1964- (Lang, 1997)
It also demonstrates how Tieck's early novellas and novels, when considered in light of the "intercontextuality" of the figures in their layered tales, suggest a much less autonomous "subject.
Zugl.: Seattle, Univ. of Washington, Diss., 1995
Keywords: Tieck, Ludwig <1773-1853> - Critique et interprétation; Tieck, Ludwig <1773-1853> -- Criticism and interpretation; Tieck, Ludwig -- 1773-1853; Individualité - Dans la littérature; Moi - Dans la littérature; Subjectivité - Dans la littérature; Wereldbeeld; Self in literature; Subjectivity in literature; Natur -- Motiv; Ich -- Motiv; Natur; Kontext; Literarische Gestalt; Ich; Hochschulschrift